Relationship Between Fractionated Signal Areas in the Atrial Muscle During Sinus Rhythm and Atrial Pacing and Non-Pulmonary Vein Foci: Novel Mapping Strategy. (August 2020) - Hirokami, Jun; Hiroshima, Kenichi; Yamaji, Kyohei; Korai, Kengo; Nagashima, Michio; Fukunaga, Masato; Morita, Junji; Yamamoto, Kei; Ando, Kenji; Goya, Masahiko
Abstract : Supplemental Digital Content is available in the text.